2014
DOI: 10.5455/musbed.20140103081933
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Tissue Factor Activities and Sialic Acid Levels in D-Galactose Induced Aging Model

Abstract: D-galaktoz ile oluşturulmuş yaşlanma modelinde doku faktörü aktivitesinin ve sialik asit miktarının değerlendirilmesi Amaç: Bu çalışmada D-galaktoz ile yaşlandırılmış, doğal yaşlı ve kontrol grubu sıçanların karaciğer ve renal dokularının doku faktörü (TF) aktivitelerinin ve inflamatuvar hastalıklar için değerli bir indikatör olan sialik asit (SA) miktarlarının ölçülmesi amaçlandı. Yöntemler: Çalışmada yirmi haftalık 28 adet Sprague-Dawley erkek rat kullanıldı. Gruplar; 1) genç kontrol grubu (n= 8), 2) doğal y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…SA is a parameter of inflammation and it is used as a measure of tissue damage (Sekili et al 1993;Kang et al 1996;Alturfan et al 2007;Ustundag et al 2014). Rajendiran et al (2013) reported a significant positive correlation between SA and high-sensitivity C-reactive protein as an inflammatory biomarker in patients with chronic cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…SA is a parameter of inflammation and it is used as a measure of tissue damage (Sekili et al 1993;Kang et al 1996;Alturfan et al 2007;Ustundag et al 2014). Rajendiran et al (2013) reported a significant positive correlation between SA and high-sensitivity C-reactive protein as an inflammatory biomarker in patients with chronic cardiac disease.…”
Section: Discussionmentioning
confidence: 99%